2006
DOI: 10.1093/hmg/ddl014
|View full text |Cite
|
Sign up to set email alerts
|

The bradykinin β2 receptor (BDKRB2) and endothelial nitric oxide synthase 3 (NOS3) genes and endurance performance during Ironman Triathlons

Abstract: We have previously shown that the insertion allele of the angiotensin-converting enzyme (ACE) gene was over-represented in the fastest South-African-born finishers of the South African Ironman Triathlons. As ACE is a component of the skeletal muscle kallikrein-kinin system (KKS), the aim of this study is to determine if there are any further associations between polymorphisms within the BDKRB2 and NOS3 genes, which encode for the KKS components, bradykinin beta(2) receptor and nitric oxide synthase, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
4
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 21 publications
2
60
4
1
Order By: Relevance
“…There were no significant differences in the frequencies of the genotype and allele distributions of the NOS3 gene G894T polymorphism between groups of triathletes classified according to finishing time into fastest (n=148), middle (n=147), slowest (n=148) and control subjects (n=203), however, the triathletes with a GG NOS3 genotype were significantly slower in the swimming and cycling phases than those possessing a 894T allele [30]. In contrast to Saunders et al [30], we did not find an association of G894T with athletic performance. There were no differences in the G894T allele frequencies in athletes stratified by the level of competitiveness (elite versus sub-elite) regardless of the athletes' status (power, "mixed" and endurance).…”
Section: Sub-elite); N -The Number Of Athletesmentioning
confidence: 82%
See 3 more Smart Citations
“…There were no significant differences in the frequencies of the genotype and allele distributions of the NOS3 gene G894T polymorphism between groups of triathletes classified according to finishing time into fastest (n=148), middle (n=147), slowest (n=148) and control subjects (n=203), however, the triathletes with a GG NOS3 genotype were significantly slower in the swimming and cycling phases than those possessing a 894T allele [30]. In contrast to Saunders et al [30], we did not find an association of G894T with athletic performance. There were no differences in the G894T allele frequencies in athletes stratified by the level of competitiveness (elite versus sub-elite) regardless of the athletes' status (power, "mixed" and endurance).…”
Section: Sub-elite); N -The Number Of Athletesmentioning
confidence: 82%
“…In contrast, Saunders et al found a significant association of this variant with endurance performance in triathletes [30]. There were no significant differences in the frequencies of the genotype and allele distributions of the NOS3 gene G894T polymorphism between groups of triathletes classified according to finishing time into fastest (n=148), middle (n=147), slowest (n=148) and control subjects (n=203), however, the triathletes with a GG NOS3 genotype were significantly slower in the swimming and cycling phases than those possessing a 894T allele [30]. In contrast to Saunders et al [30], we did not find an association of G894T with athletic performance.…”
Section: Sub-elite); N -The Number Of Athletesmentioning
confidence: 83%
See 2 more Smart Citations
“…In in-vitro luciferasebased transcription analysis, it was shown that C allele of eNOS has a lower promoter activity than T allele [6]. In previous studies, it was reported that eNOS G894T variant was associated with physical performance [23] however in another study, it wasn't found difference three variants of eNOS compared with controls [24]. When distribution of alleles is investigated, there are studies reporting that T allele is more abundant in athletes [25][26][27].…”
Section: Resultsmentioning
confidence: 99%